The triplets' secret wish - Thacker, Cathy Gillen (Harlequin special edition, 2022)
Once upon a time, designer Emma Lockhart and rancher Tom Reid were each other's one true love. Until their dueling ambitions drove them apart. Now Emma has a do-or-die opportunity that could bring the success she craves. When Tom offers his assistance in exchange for her help with his triplets, Emma can't resist the cowboy's pull on her heart...or his three little sons. Maybe her real success lies in taking a chance on happily-ever-after.